Decreasing trends in potentially inappropriate medications in older people: a nationwide repeated cross-sectional study - Solène Drusch (BMC, 2021)
Abstract Background Potentially Inappropriate Medications (PIMs) and polypharmacy are widely used indicators of suboptimal prescribing for older people. The aim of this study was to describe the changes in the prevalence of PIMs and polypharmacy among people aged 75 years and over between 2011 and 2019 in France. Methods PIMs and polypharmacy were assessed among people aged 75 years and over every two years between 2011 and 2019 using the French health insurance data system. Sixteen PIM criteria from the 2015 Beers and STOPP lists were assessed. Polypharmacy (5 to 9 drugs) and hyper-polypharmacy (≥10 drugs) were defined based on the average number of drugs dispensed per quarter. The Annual Percent Change (APC) and 95%CI were assessed using linear regression models after standardization of the prevalence on age and sex. Results The study population included 5,777,645 individuals over 75 years old in 2011 and 6,328,155 in 2019. The prevalence of PIMs decreased from 49.6 to 39.6% over the study period (APC: − 1.19% [− 1.35;-1.04]). Of the sixteen indicators assessed, the prevalence of thirteen decreased between 2011 and 2019. Benzodiazepines were the most frequent PIMs (34.7% in 2011 to 26.9% in 2019), followed by anticholinergic drugs (12.1% in 2011 to 8.3% in 2019), oral non-steroidal anti-inflammatory drugs (11.4 to 7.8%), and PIMs related to antihypertensive drugs (7.4 to 6.0%). Overall, women and individuals aged 85 years and older were more likely to receive PIMs. The prevalence of hyper-polypharmacy decreased from 30.5 to 25.9% over the study period. Conclusion This study, which is the first to assess the change in prevalence of PIMs and polypharmacy over time from comprehensive health data in France, highlights that PIMs and hyper-polypharmacy declined between 2011 and 2019. However, PIMs remains frequent for older people and often involves benzodiazepines.